Modelling of machinery vibration isolation systems - Stredulinsky, David; Szabo, Jeff; Jiang, Lei; Polack, Michael; Chernuka, Michael W. (Canadian Acoustics, 2002)
Modelling of machinery vibration isolation systems was discussed. Computer codes vibration isolation model generator (VIMGEN) and vibration of viscoelastic and elastic structures (VVES) were developed for modelling the 3D characteristics of vibration isolation systems containing elastomeric isolator elements. The engine or machine to be isolated was assumed to be a rigid body. The codes were described and a study of the modes of a small-scale system was presented.